Pendidikan Moderasi Beragama Dalam Keluaga Berbasis Al-Qur’an - Oki Setiana Dewi; Akmal Rizki Gunawan Hsb (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Religious Moderation Education in Families Based on Al-Qur'anThe purpose of this study is to analyze the theoretical concept of religious moderation education in families based on al-Qur'an. Given that the family context in the policy of strengthening religious moderation by the Ministry of Religious Affairs of Indonesia has not been a priority compared to the social and educational context. In this study, the author uses the method of tafsir maudhu'i, which serves to explore the thematic idea of